How Readiness of Students of PPG to Develop Cultural Literacy for Students in Elementary Schools ? (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Multicultural issues of racial origin, ethnic, economic, religious, social and political often occur in Indonesia for example people scorn each other and growing social media presence makes it easy for the community to pitting. The loss of the lofty values of the nation which became a major factor in the decline of civilization, compounded with the concepts in education who have been far apart from the sublime values of the nation, so an understanding of cultural literacy early need to be taught, since children at primary school age is the most fundamental in preparing the child through the cultivation of the character of sublime values contained in the local wisdom culture of Indonesia. The purpose of the research was a researcher trying to analyze how to build cultural literacy at primary school age children. A descriptive qualitative approach used in this study and the data obtained through observation, interview and question form and then the data is analyzed using the interactive model. The study was performed on students of PPG that add up to 30 people. The results of the research it is important to develop a culture of literacy began elementary school age children. Other results also show many students of PPG who know the cultural literacy, but has yet to grasp the concept of a real cultural literacy and the level of experience and understanding of students of PPG related to learning cultural literacy is also quite low. So that the right strategy and innovation are needed to develop cultural literacy.